An Examination of Uncovered Interest Rate Parity in Segmented International Commodity Markets. - Hollifield, Burton; Uppal, Raman (Journal of Finance, 1997)
The authors examine the effect of segmented commodity markets on the relation between forward future spot exchange rates in a dynamic economy. They calculate the slope coefficient in their theoretical economy from regressing exchange rate changes on forward premia. With reasonable parameter values, the slope coefficient is less than unity. However, even for extreme parameters the slope is not less than zero, as found in the data. A negative slope coefficient in a nominal version of the model requires the covariance between monetary shocks and relative output shocks to be significantly negative, in contrast to the covariance in the data.